Leaf character of sugar palm on various shades and concentrations of liquid organic fertilizer - Widarawati, Rosi; Syarifah, Risqa Naila Khusna; Prakoso, Budi (Universitas Padjadjaran, 2023)
Palm sugar has been developed to produce various products and raw materials for their derivatives. There is a very high morphological diversity of sugar palm plants, while the morphological identification of different sugar palm plant species in Banten province is still limited. The aim of this research is to determine the effect of different treatments, such as shade percentage, liquid organic fertilizer concentration, and a combination of both, on the properties of palm leaves. The experimental design used in this study was the 2-factor RCBD split plot with 3 levels each. The first factor is the variation of the shadow percentage, namely N0 (no shadow), N1 (55% shadow), and N2 (85% shadow). The second factor is different concentrations of liquid organic fertilizer (POC), namely P0 (0 ml/liter water), P1 (1 ml/liter water), and P2 (2 ml/liter water). The results showed that different types of shade yielded insignificant results in terms of variable number of leaves, total leaf area, and leaf greenness. The different types of liquid organic fertilizer concentration treatments and treatment combinations of shade percentage and liquid organic fertilizer concentrations did not influence any of the observed variables.Keywords: growth, organic fertilizer, palm, shade